Pengaruh Model Problem Based Learning (PBL) Berbasis Microsite S.id terhadap Hasil Belajar pada Materi Sistem Persamaan Linear Dua Variabel (SPLDV) - Tria Meylita Lomamay; Evi Hulukati; Auli Irfah (Lembaga Pengembangan Kinerja Dosen, 2026)
This study aimed to examine the effect of implementing the Problem-Based Learning (PBL) model integrated with the Microsite S.id platform on students' mathematics learning outcomes in the topic of Systems of Linear Equations in Two Variables (SPLDV) among ninth-grade students at SMP Negeri 1 Botupingge. The study was motivated by students' low understanding of linear equation concepts, the continued use of conventional teaching methods, and the limited utilization of interactive digital learning media. A quantitative approach was employed using a quasi-experimental method with a Pretest–Posttest Control Group Design. The sample consisted of an experimental class that received PBL supported by Microsite S.id and a control class that received PBL supported by Microsoft PowerPoint. Data were collected through pretests and posttests and analyzed using the Independent Samples t-test and effect size analysis. The results indicated that the calculated t-value (8.0131) was higher than the critical t-table value (1.688), demonstrating a statistically significant difference between the two groups. Furthermore, the effect size value of 2.6025 indicated a very large practical effect. These findings suggest that the Problem-Based Learning model integrated with Microsite S.id is more effective in improving students' mathematics learning outcomes than PBL supported by Microsoft PowerPoint while promoting more interactive, contextual, and problem-solving-oriented learning experiences.